2019
DOI: 10.1177/0269881118821113
|View full text |Cite
|
Sign up to set email alerts
|

Alternation in dopamine D2-like and metabotropic glutamate type 5 receptor density caused by differing housing conditions during abstinence from cocaine self-administration in rats

Abstract: Background: Environmental conditions have an important function in substance use disorder, increasing or decreasing the risks of relapse. Several studies strongly support the role of the dopamine D2-like and metabotropic glutamate type 5 receptors in maladaptive neurobiological responses to cocaine reward and relapse. Aims: The present study employed cocaine self-administration with yoked-triad procedure in rats to explore whether drug abstinence in different housing conditions affects the drug-seeking behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 82 publications
2
12
0
Order By: Relevance
“…Based on substantial evidence demonstrating that environmental enrichment such as social housing attenuates drug seeking across different drug classes ( Thiel et al, 2009 , 2010 ; Hofford et al, 2014 ; Imperio et al, 2018 ; Frankowska et al, 2019 ; Westenbroek et al, 2019 ; Cho et al, 2020 ; Grimm and Sauter, 2020 ; Mastrogiovanni et al, 2021 ), we were interested in examining whether this is also the case in our study. Note that different from most studies in which housing condition is manipulated only during abstinence periods, here the manipulation of housing condition started after intravenous surgeries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on substantial evidence demonstrating that environmental enrichment such as social housing attenuates drug seeking across different drug classes ( Thiel et al, 2009 , 2010 ; Hofford et al, 2014 ; Imperio et al, 2018 ; Frankowska et al, 2019 ; Westenbroek et al, 2019 ; Cho et al, 2020 ; Grimm and Sauter, 2020 ; Mastrogiovanni et al, 2021 ), we were interested in examining whether this is also the case in our study. Note that different from most studies in which housing condition is manipulated only during abstinence periods, here the manipulation of housing condition started after intravenous surgeries.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we followed up on this finding with the second experiment using group-housed rats. This is based on numerous studies demonstrating that social experience (e.g., social play) contributes to neurobehavioral development in adolescent rats ( Vanderschuren et al, 2016 ; Burke et al, 2017 ) and environmental enrichment involving social housing attenuates drug seeking in adult rats ( Thiel et al, 2009 , 2010 , 2012 ; Hofford et al, 2014 ; Imperio et al, 2018 ; Frankowska et al, 2019 ; Mastrogiovanni et al, 2021 ). In particular, previous studies found that the single-housing condition offsets the age difference in incubation of cocaine craving, an effect observed in pair-housed rats ( Li and Frantz, 2009 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the fact that the basal level of Munc13 was not changed under different conditions of cocaine abstinence in yoked saline (control) rats, as well as that Munc13 levels were not altered in rats previously administered cocaine in other cocaine abstinence procedures than rats housed in an enriched environment, one can suppose that increased level of Munc13 is probably as a result of the combination of an enriched environment and cocaine and enriched environment enhances the cocaine-induced motivation-driven learning. After abstinence in an enriched environment, a reduction in drug seeking behavior to the conditioned stimulus [38,39] and cocaine priming [39] was reported. This type of drug forced abstinence-in contrast to extinction training under the contexts/environments where the original memories were formed-makes extinction memories generalize to other contexts.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, rats housed in an enriched environment continued to avoid intake of the cocaine-associated saccharin cue [40]. Moreover, it was shown that extinction training and enriched environment attenuated cue-induced cocaine-seeking behavior [39,41], while the combined therapy using the extinction training with an enriched environment completely prevented it [41]. Environmental enrichment differentially regulates the response to psychostimulants in the nucleus accumbens shell and core by modulation of DAT function [42].…”
Section: Discussionmentioning
confidence: 99%
“…Cocaine Self-Administration Female offspring at PND 63 began lever pressing for cocaine reinforcement during the 2-h daily sessions performed six days/week (maintenance) for a total of three weeks, and from that time, they were given free access to food throughout the remainder of the experiment. Rats were trained to self-administer cocaine in described previously [25] standard operant chambers (Med-Associates, Fairfax, VT, USA) in contact with an infusion pump (Model 3.33 RPM, Med-Associates, Fairfax, VT, USA) according to two experimental protocols: (a) a stable dose of cocaine (0.5 mg/kg/infusion) and an increased schedule of reinforcement (FR1-5) or (b) increased cocaine doses (0.25-1 mg/kg/infusion) and a stable FR1 schedule of reinforcement. Each schedule was completed by pressing the "active" lever resulting in a 5 s infusion of cocaine and a 5 s presentation of the stimulus complex, which consisted of an activation of the white stimulus light directly above the "active" lever and a tone from the generator (2000 Hz; 15 dB above the ambient noise level).…”
Section: Cocaine Self-administration Proceduresmentioning
confidence: 99%